Transformational Leadership Model of School Principals in Strengthening Civic Values: A Case Study at Erlangga Senior High School - Michael Fredrik Sihombing; Immanuel Onasis Kha Napitupulu; Ferry Deni Doloksaribu; Yesica Febrianti Tambunan; Pinka Laura Malau; Ropinus Sidabutar (Yayasan Bayt Shufiya Nusantara, 2025)
This study examines the role of transformative leadership exercised by the school principal in strengthening civic values at SMA Swasta Erlangga Pematangsiantar. Employing a qualitative case study approach, the research explores leadership strategies, implementation processes, and challenges in fostering an inclusive and adaptive school culture within a small-scale private school context. Data were collected through in-depth interviews, focus group discussions, and participatory observation involving the principal, teachers, and students. The findings reveal that transformative leadership, manifested through moral role modeling, inspirational motivation, intellectual stimulation, and individualized consideration, effectively enhances the involvement of teachers, students, parents, and the surrounding community in internalizing civic values. These values are reflected in collaborative learning practices, student organizational activities, and school–community partnerships. Despite challenges such as social media influence, limited resources, and varying parental expectations, transformative leadership functions as a significant agent of change in addressing the demands of the digital era and social diversity. The study concludes that continuous leadership development and strengthened school–community collaboration are essential to optimizing civic education.